A new marine mammal assemblage from central Chile reveals the Pliocene survival of true seals in South America. (2nd November 2022) - Benites-Palomino, Aldo; Valenzuela-Toro, Ana M.; Figueroa-Bravo, Constanza; Varas-Malca, Rafael M.; Nielsen, Sven N.; Gutstein, Carolina Simon; Carrillo-Biceño, Jorge D.
ABSTRACT: The fossil record of marine mammals from the upper Pliocene of the western coast of South America is poorly known, hindering our knowledge about how and when marine mammal faunas attained their modern distribution in the area. Here, we describe a new marine mammal assemblage from the Horcón Formation (upper Pliocene), located in the Valparaíso Region of central Chile. The material reported comprises postcranial remains of an indeterminate seal (Phocidae), Delphinoidea vertebrae, and mysticete elements (still in the field). The Phocidae remains constitute the youngest pre-Pleistocene record of this family in South America, providing new information regarding the timing for the establishment of the modern diversity and distribution of pinnipeds in the Southern Hemisphere. Furthermore, the pinniped and cetacean remains reported indicate that the marine mammal assemblage from the upper Pliocene along central Chile was composed of a mixture of modern and extinct taxa.